PENGARUH WORK LIFE BALANCE DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN - Ayrton Maurits Willem; Wilson Bangun (Value : Jurnal Manajemen dan Akuntansi, 2023)
During The reign of Joko Widodo, there were various government strategic projects that were required to be completed before 2024, including the Cisumdawu Toll Road Development Project. Employee performance is a factor that is closely related to the successful completion of these projects. Work life balance and emotional intelligence are a stimulus to employee performance. To determine the effect of work life balance and emotional intelligence on employee performance is the aim of this study. As a material consideration for purchasing the company's strategy in improving employee performance is the expected benefit of the research conducted.. Quantitative research method is a research method used with a saturated sample of 115 employees of PT. Adhi Karya (Persero) Tbk. those involved in the Cisumdawu toll road construction project were samples in the study. Structural Equation Model - Partial Least Square is used as a data processing method in this study. This study found that there is an influence of work life balance on employee performance. Emotional intelligence has no effect on employee performance. Keywords: work life balance, emotional intelligence, employee performance